Anxiety and psychosocial impact during coronavirus disease 2019 in home dialysis patients. Issue 2 (6th October 2021) - Davis, Michael J.; Alqarni, Khaled A.; McGrath‐Chong, Margaret E.; Bargman, Joanne M.; Chan, Christopher T.
Abstract: The severe acute respiratory syndrome coronavirus (SARS‐Cov‐2) resulting in the coronavirus disease 2019 (COVID‐19) is documented to have a negative psychosocial impact on patients. Home dialysis patients may be at risk of additional isolating factors affecting their mental health. The aim of this study is to describe levels of anxiety and quality of life during the COVID‐19 pandemic among home dialysis patients. This is a single‐centre survey of home dialysis patients in Toronto, Ontario. Surveys were sent to 98 home haemodialysis and 43 peritoneal dialysis patients. Validated instruments (Haemodialysis and Peritoneal Dialysis Treatment Satisfaction Questionnaire, Generalized Anxiety Disorder 7 Item [GAD7] Scale, Patient Health Questionnaire [PHQ‐9], Illness Intrusiveness Ratings Scale, Family APGAR Questionnaire and The Self Perceived Burden Scale) assessing well‐being were used. Forty of the 141 patients surveyed, participated in September 2020. The mean age was 53.1 ± 12.1 years, with 60% male, and 85% home haemodialysis, 80% of patients rated their satisfaction with dialysis at 8/10 or greater, 82% of respondents reported either "not at all" or "for several days" indicating frequency of anxiety and depressive symptoms, 79% said their illness minimally or moderately impacted their life, 76% of respondents were almost always satisfied with interactions with family members, 91% were never or sometimes worried about caregiver burden. Among our respondents, there was no indication of a negative psychosocial impact from the pandemic, despite the increased social isolation. Our data further supports the use of home dialysis as the optimal form of dialysis. SUMMARY AT A GLANCE: This survey of home haemodialysis or peritoneal dialysis patients found no indication of a negative psychosocial impact from the COVID‐19 pandemic, despite the increased social isolation. Thus, patients who are able to practise dialysis at home and hence minimize infectious contacts do not experience high levels of psychosocial distress, adding to the paradigm of home dialysis as the optimal form of dialysis.